2007
DOI: 10.1111/j.1471-4159.2007.04633.x
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin suppresses growth and chemoresistance of human glioblastoma cells via AP‐1 and NFκB transcription factors

Abstract: Malignant gliomas are a debilitating class of brain tumors that are resistant to radiation and chemotherapeutic drugs, contributing to the poor prognosis associated with these tumors. Over-expression of transcription factors such as NFjB and AP-1 contribute to the enhanced glioma survival, radioresistance, and chemoresistance. Curcumin, which may inhibit these pathways, was therefore investigated for a potential therapeutic role in glioma. The effect of curcumin on glioma survival was investigated in human (T9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
186
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 279 publications
(197 citation statements)
references
References 68 publications
8
186
0
3
Order By: Relevance
“…Arrest of the cell cycle at the G2/M phase is one of the effects of curcumin found in this study, which is in agreement with our previous finding in breast cancer MDA-MB-231 cells, findings in human glioma U87 cells by Pratibha et al, and Liu et al in human glioma U251 cells (4,7,16). This event was considered to be derived from up-regulation of p53, which has been identified as a common target of curcumin in different cancers.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Arrest of the cell cycle at the G2/M phase is one of the effects of curcumin found in this study, which is in agreement with our previous finding in breast cancer MDA-MB-231 cells, findings in human glioma U87 cells by Pratibha et al, and Liu et al in human glioma U251 cells (4,7,16). This event was considered to be derived from up-regulation of p53, which has been identified as a common target of curcumin in different cancers.…”
Section: Discussionsupporting
confidence: 83%
“…In malignant brain tumors, curcumin also exhibits its pleiotropic activity, which includes inducing cell cycle arrest at the G2/M stage through up-regulation of ING4, suppressing tumor growth by inhibition of AP-1 and NF-κB, and inhibiting anti-apoptotic signaling by increasing the Bax to Bcl-2 ratio (7)(8)(9). Nevertheless, most failure of cancer therapy in clinical practice is attributed to the polymorphism of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…However, Cur at 10 μM concentration decreased the HSP90 level but the 1 μM concentration did not affect the HSP90 levels. The HSP90 level may have been reduced at 10 μM (Figure 2), because this concentration can induce neuronal death [46,47]. In our experiment, we observed that higher concentration (≤ 10 μM) induced neuronal apoptosis, whereas lower concentration especially nanomolar to 1 μM of Cur is neuroprotective.…”
Section: Although the Mechanistic Details Of Neuroprotection By Cur Isupporting
confidence: 53%
“…In our experiment, we observed that higher concentration (≤ 10 μM) induced neuronal apoptosis, whereas lower concentration especially nanomolar to 1 μM of Cur is neuroprotective. It has been reported that higher concentration of Cur can induce neuronal apoptosis and act as an anti-cancer agent [46][47][48]. Although the mechanistic details of how Cur restored HSPs after Aβ42 exposure, or how they induce HSPs in SH-SY5Y cells, is still unclear to us, one possible explanation may be that Cur treatments confer neuroprotection by secreting several growth factors, including BDNF, NGF and IGF [49][50][51].…”
Section: Although the Mechanistic Details Of Neuroprotection By Cur Imentioning
confidence: 95%
“…Many tumors demonstrate good responsiveness to this drug, but drug resistance eventually develops, particularly in patients with lung, colorectal, prostate and ovarian cancer (22). Several approaches have been proposed to maintain cisplatin efficacy, including increased accumulation or stabilization of p53, upregulating reactive oxygen species production and inhibiting NF-κB and antiapoptotic proteins (23)(24)(25)(26). The current study investigated the effects of apigenin on p53 accumulation, and its effect on cisplatin Apigenin enhances the cisplatin cytotoxic effect through p53-modulated apoptosis or cisplatin (in PBS).…”
Section: Introductionmentioning
confidence: 99%